MERANCANG STRUKTUR KEILMUAN PAI YANG ADAPTIF DALAM PENGGUNAAN TEKNOLOGI INFORMASI DIGITAL - Sabrina Izzatul Jannah; Irawan Irawan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The rapid development of digital information technology has changed the educational paradigm, including in Islamic Religious Education (PAI), which demands an adaptive scientific structure to optimize learning potential. This study aims to design an PAI scientific structure relevant to digital dynamics and formulate an implementation strategy. Using a qualitative approach with secondary data analysis from scientific journals, reports, and interviews, this study explores the integration of technology in the PAI curriculum. The findings indicate that the use of digital platforms such as Google Classroom, Zoom, and interactive quiz applications significantly increases student engagement and understanding of the material. As empirical evidence, in one school in Jakarta, the integration of digital learning applications was proven to boost students' final exam scores by up to 20% compared to conventional methods. Furthermore, technology facilitates independent and collaborative learning through social media, which enriches students' religious insights. The main conclusion of this study confirms that the transformation of the PAI curriculum that is responsive to technology, balanced with digital literacy and ethics, is a crucial step to increase learning effectiveness and prepare the younger generation of Muslims to face global challenges. ABSTRAK Perkembangan teknologi informasi digital yang pesat telah mengubah paradigma pendidikan, termasuk dalam Pendidikan Agama Islam (PAI), yang menuntut adanya struktur keilmuan yang adaptif guna mengoptimalkan potensi pembelajaran. Penelitian ini bertujuan merancang struktur keilmuan PAI yang relevan dengan dinamika digital dan merumuskan strategi implementasinya. Menggunakan pendekatan kualitatif dengan analisis data sekunder dari jurnal ilmiah, laporan, dan wawancara, penelitian ini mengeksplorasi integrasi teknologi dalam kurikulum PAI. Temuan menunjukkan bahwa pemanfaatan platform digital seperti Google Classroom, Zoom, dan aplikasi kuis interaktif secara signifikan meningkatkan keterlibatan siswa dan pemahaman materi. Sebagai bukti empiris, di salah satu sekolah di Jakarta, integrasi aplikasi pembelajaran digital terbukti mendongkrak nilai ujian akhir siswa hingga 20% dibandingkan metode konvensional. Selain itu, teknologi memfasilitasi pembelajaran mandiri dan kolaboratif melalui media sosial, yang memperkaya wawasan keagamaan siswa. Simpulan utama penelitian ini menegaskan bahwa transformasi kurikulum PAI yang responsif terhadap teknologi, diimbangi dengan literasi digital dan etika, merupakan langkah krusial untuk meningkatkan efektivitas pembelajaran dan mempersiapkan generasi muda Muslim menghadapi tantangan global.